Recovery strategies to optimize range of motion and activities of daily living following total knee replacement in Saudi Arabia: A narrative review - Irma Liana Putri; Edy Soesanto; RNgt Amin Samiasih (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Knee osteoarthritis is highly prevalent among older adults in Saudi Arabia, with reported estimates ranging from 41% to 79%, and Total Knee Replacement (TKR) remains the definitive surgical treatment once conservative management fails. However, the long-term success of TKR depends heavily on structured post-operative rehabilitation, since surgical correction alone does not guarantee functional recovery. Purpose: This narrative review synthesizes current clinical evidence on recovery strategies following TKR, with particular emphasis on Range of Motion (ROM) progression, early mobilization, and Activities of Daily Living (ADL) recovery, while also considering the specific functional demands of the Saudi Arabian clinical context, including the high knee-flexion range required for Islamic prayer (Salah). Method: This narrative review followed the SANRA (Scale for the Assessment of Narrative Review Articles) guideline. A structured search of PubMed, MEDLINE, CINAHL, Scopus, PEDro, and Google Scholar was conducted for literature published between 2015 and 2026 using combinations of the terms "total knee replacement," "range of motion," "activities of daily living," and "rehabilitation." After screening against pre-defined inclusion and exclusion criteria, 16 peer-reviewed sources addressing TKR rehabilitation, ROM, ADL, and enhanced recovery protocols were retained for narrative synthesis. Results: Three clinically oriented themes emerged: (1) early, structured rehabilitation protocols, including Enhanced Recovery After Surgery (ERAS) pathways and progressive passive-to-active ROM exercises, which reduce arthrofibrosis and accelerate functional recovery; (2) standardized outcome measurement using goniometry, the Barthel Index, and the WOMAC index to monitor ROM, pain, and ADL independence; and (3) rehabilitation targets adapted to the Saudi Arabian context, particularly the 130°-140° flexion range required for prostration during prayer, alongside strengthening exercises, gait training, and adherence support. Conclusion: Early, structured, and culturally responsive rehabilitation is central to optimizing ROM and ADL outcomes after TKR in Saudi Arabia. Clinicians should prioritize early mobilization, individualized ROM targets that account for religious and cultural practice, and standardized outcome tracking, while future prospective studies should quantify long-term functional recovery in Saudi TKR populations.